تأثير استعمال جيزان الاقتران القابلة للاستبدال على تخفيض الأثر الزلزالي وتبديد الطاقة في المباني العالية الهجينة، الناتجة عن اقتران جدران القص البيتونية المسلحة مع جيزان فولاذية رابطة (Latakia University Journal -Engineering Sciences Series, 2019)
The expected shear strength and deformation required on the coupling beams associated with medium and high-rise installations during the earthquake event require the conversion of conventional anti collapse design to a repairable design in some important structures. The simplest way to achieve a repairable design is to put some replaceable structural elements in appropriate locations, while the whole structure remains functioning as an integrated system. A group of researchers has presented studies in the behavior of replaceable fuse within the steel coupling beams by means of testing and analysis. The results of the experimental and analytical studies by pushover analysis showed that the new replaceable coupling beams have the ability to absorb and dissipate large amounts of earthquake energy before failure. The research aims to study the effect of the use of replaceable coupling beams on the reduction of earthquake impact and energy dissipation in high hybrid buildings, resulting from the coupling of reinforced concrete shear walls with bonded steel beams by calibrating an analytical model using ANSYS 16 with experimental results in this field and monitoring performance earthquake correlations associated with the results of modeling and pushover analysis. The results of the pushover analysis show, that the damage to the replaceable coupling beams focused on the "fuse", while the remaining parts of the coupling beam kept elastic. This was beneficial to repair after earthquake. In contrast, the damage to the conventional coupling beams focused on the end of beam, which was difficult to repair after earthquake. تأثير استعمال جيزان الاقتران القابلة للاستبدال على تخفيض الأثر الزلزالي وتبديد الطاقة في المباني العالية الهجينة، الناتجة عن اقتران جدران القص البيتونية المسلحة مع جيزان فولاذية رابطة تتطلب مستلزمات قوة القص والتشوه المتوقعة على الجيزان المقترنة في المنشآت متوسطة وعالية الارتفاع خلال الحدث الزلزالي تحويل طريقة التصميم التقليدية المضادة للانهيار لطريقة تصميم قابلة للإصلاح في بعض الهياكل الهامة. تعتبر أبسط طرق تحقيق تصميم قابل للإصلاح هو بوضع بعض العناصر الإنشائية القابلة للاستبدال في مواقع مناسبة، بينما يبقى كامل الهيكل يعمل كنظام متكامل. قدمت مجموعة من الباحثين دراسات في سلوك فاصمة قابلة للاستبدال ضمن الجيزان المعدنية المقترنة عن طريق الاختبار والتحليل. بينت نتائج الدراسات التجريبية والتحليلية بطريقة التحليل الستاتيكي اللاخطي، أن الجيزان المقترنة الجديدة القابلة للاستبدال "الفاصمة" تمتع بقدرة عالية على امتصاص وتبديد كميات كبيرة من الطاقة الزلزالية قبل فشلها. يهدف البحث لدراسة تأثير استعمال جيزان الاقتران القابلة للاستبدال على تخفيض الأثر الزلزالي وتبديد الطاقة في المباني العالية الهجينة، الناتجة عن اقتران جدران القص البيتونية المسلحة مع جيزان فولاذية رابطة، وذلك من خلال معايرة نموذج تحليلي باستعمال برنامج ANSYS 16 مع نتائج تجريبية ضمن هذا المجال ورصد الأداء الزلزالي للجيزان المقترنة من نتائج النمذجة والتحليل الستاتيكي اللاخطي. تظهر نتائج التحليل الستاتيكي اللاخطي تركز الضرر لجيزان الاقتران القابلة للاستبدال على "الفاصمة"، في حين تبقى الأجزاء الأخرى لجائز الاقتران مرنة. يعتبر هذا مفيداً للإصلاح بعد الزلزال. في المقابل، تركز الضرر لجيزان الاقتران التقليدية في نهاية الجائز، والذي كان من الصعب إصلاحه في مرحلة ما بعد الزلزال.